Effect of Ca, Sr and Ba distribution on the relaxor properties of CSBN single crystals. (26th April 2017) - Malyshkina, O.; Ivanova, A.; Malyshkin, Y.; Folomeeva, A.; Shashkov, M.; Dec, J.
ABSTRACT: In the present work, we aimed to find the correlation between the distribution of Ca, Ba and Sr over the volume and ferroelectric properties of CSBN materials. As a result, it is shown that in the CSBN25 which is characterized by relaxor properties there exists smaller excess oxygen compared with CSBN50 and CSBN75 crystals. CSBN25 also have more nonuniform distribution of elements, which occupy the same position (A1) in tetragonal tungsten bronze structure.